Transit Migration and Crime: Evidence from Colombia - Ramón Rey; Günther G. Schulze; Nikita Zakharov (Center for Economic Studies and ifo Institute (CESifo), 2024)
This paper investigates the effect of Venezuelan transit migration on crime rates in Colombia. We exploit the reopening of the Venezuela-Colombia border in 2016, which has led to a surge in transit migration, and geospatial information about the distinct routes through which the migrants crossed Colombia. Employing a difference-in-differences approach and propensity score matching, we find that transit migration increased property crime rates in crossed municipalities, with both native Colombians and Venezuelan refugees seeing higher victimization rates. Violent crimes remained unaffected. This is the first study to document a link between transit migration and crime.
Keywords: K42; F22; 330; transit migration; crime; migration